2023
DOI: 10.24875/gmm.m17000024
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma and its effect in bone regeneration in mandibular fractures. Controlled clinical trial

Abstract: ResumenAntecedentes: Actualmente existe interés en el desarrollo de aplicaciones clínicas del plasma rico en plaquetas (PRP) para mejorar la regeneración ósea (RO). Objetivo: Evaluar la RO en fracturas mandibulares con la aplicación de PRP. Métodos: Ensayo clínico controlado. Se incluyeron 20 pacientes con fractura de ángulo mandibular. El grupo de estudio (n = 10) se sometió a reducción de la fractura, fijación interna y aplicación de PRP, y el grupo control (n = 10) al mismo procedimiento sin administración … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…As shown in Table 1 , the study of Rodriguez and Urso [ 15 ] was scored 3, which was assessed as a low-quality clinical trial. RCTs with a literature score greater than 3 are considered high-quality clinical trials 3 (Daif [ 16 ], Samy [ 17 ], and Namazi and Mehbudi [ 18 ]), 2 (Wei et al [ 19 ] and Griffin et al [ 10 ]), and 4 (Al-Khawlani et al [ 20 ], Ghaffarpasand et al [ 21 ], Singh et al [ 11 ], and Castillo et al [ 22 ]) clinical trials, respectively. In addition, Review Manager 5.3 software was used to assess the quality of the trials, including the risk of bias graph ( Figure 2 ) and risk of bias summary ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1 , the study of Rodriguez and Urso [ 15 ] was scored 3, which was assessed as a low-quality clinical trial. RCTs with a literature score greater than 3 are considered high-quality clinical trials 3 (Daif [ 16 ], Samy [ 17 ], and Namazi and Mehbudi [ 18 ]), 2 (Wei et al [ 19 ] and Griffin et al [ 10 ]), and 4 (Al-Khawlani et al [ 20 ], Ghaffarpasand et al [ 21 ], Singh et al [ 11 ], and Castillo et al [ 22 ]) clinical trials, respectively. In addition, Review Manager 5.3 software was used to assess the quality of the trials, including the risk of bias graph ( Figure 2 ) and risk of bias summary ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of PRP on bone mineral density during the treatment of mandibular fractures has been studied in three clinical experiments: Al-Khawlani et al [ 20 ], Castillo et al [ 22 ], and Daif [ 16 ]. As shown in Figure 4 , there was no heterogeneity between these three studies ( I 2 = 0%, P = 0.20), and the PRP increased bone mineral density in the fracture trace and shorted the time of bone regeneration in mandibular fractures patients (SMD = −1.99, 95%CI = −2.64–−1.35).…”
Section: Resultsmentioning
confidence: 99%
“…From this view, platelet concentrates that enrich high concentrations of platelets after centrifugation may provide many types of platelet-derived growth factors [6], which can promote angiogenesis and the regeneration of tissue [7][8][9][10]. Platelet-rich plasma (PRP) has been the most commonly used type of platelet concentrate, and the use of PRP in AGA has been investigated in numerous clinical studies focusing on hair loss, but the results have been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and vivo experiments also confirmed that growth factors are involved in the regulation of hair follicle growth and development and hair cycle, such as vascular endothelial growth factor (VEGF), insulin-like growth factor (IGF-1), and fibroblast growth factor (FGFs) [2][3][4][5]. Thus, platelet concentrates can be defined as autologous concentrations of platelet-derived growth factors in the plasma [6] that are released by activated platelets after centrifugation, with these factors promoting angiogenesis, cell proliferation and differentiation in the processes of soft-and hard-tissue wound healing [7][8][9][10]. Moreover, various studies have shown that platelet concentrates can induce the proliferation of the dermal papilla, prolong the anagen phase and increase the vascularization around hair follicles, thus leading to a positive trend in hair growth [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies using PRP to treat a variety of bone injuries, for example in the treatment of extraction socket [39,49], humeral shaft fractures [44], mandibular fractures [38,43], non-union fractures [40,42] and others. The majority of these studies did not quantify the number of platelets and leukocytes and it was difficult to classify the type of PRP (Table 1).…”
Section: Platelet-rich Plasma (Prp)mentioning
confidence: 99%